Challenges and prospects of linked data technology: a qualitative study of Pakistani LIS professionals' insights. Issue 2 (20th August 2021) - Warraich, Nosheen Fatima; Rasool, Tayayba; Rorissa, Abebe
Abstract : Purpose: This study aims to explore the perceived challenges and prospects of linked data (LD) technology along with the skills required among library professionals to take LD initiatives in Pakistani libraries. Design/methodology/approach: A qualitative research design with the phenomenology approach was used to meet the objectives of the study. Data was collected through in-depth interviews from 18 senior libraries and information science (LIS) professionals who were well versed with technology. This sample consisted of informants who provided rich and privileged information about the topic and had been involved in the implementation of new technologies in libraries. Qualitative data analysis software NVivo was used to analyze data and to create themes. Findings: Results indicated that LIS professionals should have advanced technical skills to adopt LD technology in their libraries. Respondents opined that the visibility of library resources and services should be increased on the Web for a wider audience. Findings identified the following challenges in the implementation of LD initiatives in the information environment: MARC standards, low level of awareness, lack of skills among professionals, privacy issues and time barrier. Moreover, information professionals have been contending uncertainties to implement emergent technologies in libraries. However, they are still willing to adopt LD technologies, though these initiatives are at an infancy level in libraries. Social implications: Findings may be helpful and supportive for professional associations to design training content and for library schools for offering advanced technology courses. Originality/value: This study will contribute to LIS literature especially in the context of developing countries. It will enhance library professionals' awareness regarding the significance of LD initiatives in libraries.